The role of sleep disturbances in associations between early life adversity and subsequent brain and language development during childhood - Lara, Hatty; Nevarez-Brewster, Melissa; Manning, Cori; Reid, Matthew J.; Parade, Stephanie H.; Mason, Gina M.; Rojo-Wissar, Darlynn M. (Frontiers in Sleep, 2024)
Sleep disturbances are posited to play a key role in the development of poor mental and physical health outcomes related to early life adversity (ELA), in part through effects on brain development. Language development is critically important for health and developmental outcomes across the lifespan, including academic achievement and emotion regulation. Yet, very little research has focused on the dynamic contributions of ELA, sleep, and brain development on language outcomes. In this mini review, we summarize the current pediatric literature independently connecting ELA and sleep to language development, as well as the effects of ELA and sleep on language-relevant aspects of brain structure and function. We then propose a framework suggesting that sleep disturbances and subsequent effects on brain structure and function may act as key mechanisms linking ELA and language development. Future research investigating the associations among ELA, sleep, brain, and language development will refine our proposed framework and identify whether sleep should be included as an intervention target to mitigate the effects of early life adversity on language development.